1353 Insulin-Treated Hyperglycaemia is Associated with Lower Amino Acid Levels in Very Preterm Infants Receiving Parenteral Nutrition. (October 2012) - Mayes, K; Tan, M; Morgan, C
Abstract : Background: Hyperalimentation describes the increase in glucose, amino acid (AA) and lipid intake designed to overcome postnatal growth failure in preterm infants. We have previously shown increasing parenteral AA intake increased 14/22 individual AA levels with only tyrosine lower. Hyperalimentation increases hyperglycaemia requiring insulin treatment. We hypothesised insulin administration may increase AA utilisation so lowering AA levels. Aim: To compare the plasma AA profiles in preterm infants with insulin-treated hyperglycaemia with those whose did not receive insulin. Methods: Infants < 29 weeks gestation were originally randomised to receive hyperalimentation (25% more glucose, 4g/kg/day versus 3g/kg/day protein/lipid) or a control regimen within 5 days of birth with head growth as the primary outcome. The study protocol recorded actual nutrient intake and parenteral nutrition "intolerance" including hyperglycaemia, insulin use and AA profiles. AA levels were measured on day 9 (ion exchange chromatography). Results: 118 AA profiles were obtained from 142 infants on day 8–10. Secondary analysis restratified data to compare insulin (n=57; hyperalimentation n=37) with no insulin (n=61; hyperalimentation n=20) treatment. Infants receiving insulin were of lower gestation/birthweight (p<0.01) and received more protein (3.0g/kg/day versus 2.7g/kg/day; p=0.02) mainly as intravenous AA, when compared to those not receiving insulin. The insulin-treated group had lower levels in 9/22 AAs (p<0.05) and no statistically significant difference in the remaining 13 (p>0.05). Conclusion: Preterm infants with insulin-treated hyperglycaemia have lower AA levels on day 8–10 despite lower birthweight, gestation and higher protein intake. This suggests exogenous insulin may improve AA utilisation for protein synthesis.